Calculation of Range and Angle Error for Space Surveillance Radar Using Two-Dimensional Refractive Indices of the Troposphere and Ionosphere - Junmo Yang; Do Hyeon Lee; Sangho Lim; Ik Hwan Choi; Yong Bae Park (Journal of Electromagnetic Engineering and Science)
This paper proposes a method for accurately estimating the position of space objects by accounting for atmospheric effects on electromagnetic (EM) wave propagation. To predict the propagation characteristics in the atmosphere, the refractive indices of the troposphere and ionosphere are modeled using meteorological data, interpolation techniques, and an ionospheric electron density model. In addition, ray tracing is employed to analyze the propagation path and speed of EM waves in the atmosphere. The range and angle errors of the space surveillance radar are quantitatively calculated by considering the characteristics of the EM waves propagating through the atmosphere. To ensure accuracy, the atmosphere is modeled based on the meteorological variables and ionospheric electron density available at the time the radar echo is received. Furthermore, alternatives are proposed for cases where such variables are unavailable.